Strengthening Social Cohesion, Conflict Management, and Diversity Education through the Implementation of Social Studies Education - Chia, Esther; Abdulsamad, Aliyu (COMPETITIVE: Journal of Education, 2025)
Social cohesion, conflict management and diversity education are essential components that should be included in any educational curriculum that is designed to cater for multifaceted societies. The Social Studies curriculum that is included in the National Certificate of Education (NCE) in Nigeria is designed to meet these components. On the other hand, the effectiveness of the curriculum in terms of achieving these goals has been the subject of many discussions. For the purpose of determining whether or not the curriculum is efficient in fostering abilities related to social cohesion, conflict management, and diversity, a survey was carried out among students studying Social Studies in Colleges of Education in North-West Nigeria. A comprehensive analysis of the National Certificate in Education (NCE) Social Studies curriculum in Nigeria is presented here, focusing on both its strengths and areas that could use some work. As part of the evaluation process, the effectiveness of the curriculum in developing skills related to social cohesion, conflict management, and diversity is assessed. A number of suggestions are offered in order to improve the curriculum and better prepare future educators for the multifaceted society that exists in Nigeria. According to the findings of the study, there is a pressing need for a more direct emphasis on conflict management skills, negotiation skills, and an appreciation for diversity